Morning NO2 exposure sensitizes hypertensive rats to the cardiovascular effects of same day O3 exposure in the afternoon. (20th March 2016) - Farraj, Aimen K.; Malik, Fatiha; Haykal-Coates, Najwa; Walsh, Leon; Winsett, Darrell; Terrell, Dock; Thompson, Leslie C.; Cascio, Wayne E.; Hazari, Mehdi S.
Abstract: Context : Within urban air sheds, specific ambient air pollutants typically peak at predictable times throughout the day. For example, in environments dominated by mobile sources, peak nitrogen dioxide (NO2 ) levels coincide with morning and afternoon rush hours, while peak levels of ozone (O3 ), occur in the afternoon. Objective : Given that exposure to a single pollutant might sensitize the cardiopulmonary system to the effects of a subsequent exposure to a second pollutant, we hypothesized that a morning exposure to NO2 will exaggerate the cardiovascular effects of an afternoon O3 exposure in rats. Materials and methods : Rats were divided into four groups that were each exposed for 3 h in the morning (m) and 3 h in the afternoon (a) on the same day: (1) m-Air/a-Air, (2) m-Air/a-O3 (0.3 ppm), (3) m-NO2 (0.5 ppm)/a-Air and (4) m-NO2 /a-O3 . Implanted telemetry devices recorded blood pressure and electrocardiographic data. Sensitivity to the arrhythmogenic agent aconitine was measured in a separate cohort. Results : Only m-NO2 /a-O3 -exposed rats had significant changes in electrophysiological, mechanical and autonomic parameters. These included decreased heart rate and increased PR and QTc intervals and increased heart rate variability, suggesting increased parasympathetic tone. In addition, only m-NO2 /a-O3 exposure decreased systolic and diastolic blood pressures and increased pulse pressure and QA interval, suggesting decreased cardiac contractility. Discussion and conclusion : The findings indicate that initial exposure to NO2 sensitized rats to the cardiovascular effects of O3 and may provide insight into the epidemiological data linking adverse cardiovascular outcomes with exposures to low concentrations of O3 .